ANALISIS PLOT DALAM NOVEL DI SINI CINTA PERTAMA KALI BERSEMI KARYA MIRA. W - GWIJANGGE, ANTINA; PALIT, ANATJE TINNEKE; PUA, CHRISTO RILCO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research conveys how literature works, especially novels that understand the personality of the main character. This study answers two problems, namely: (1) What is the character of the main character in the novel â€œDi sini Cinta Pertama Kali Bersemi ? (2) What moral message do the authors want to convey through the novel Di sini Cinta Pertama Kali Bersemi?The method used in this research is descriptive analysis method. In this method the researcher divides the activity into 2 stages: first, analyzing the sosychological approach of the main character Di sini Cinta Pertama Kali Bersemi based on character theory according to Hippocrates and Galenus. The second analyzes moral messages based on attitude, behavior and karmic order in the novel â€œDi siniÂ  Cinta Pertama Kali Bersemiâ€..The data source of this research is the novel "translated by Disini Cinta Pertama Kali Bersemiâ€ 1990. It is 300 pages long and was first published by the Indonesian Torch Foundation, a member of IKAPI DKI Jakarta. This research is in the form of direct and indirect quotes contained in the novel Di sini Cinta Pertama Kali Bersemi.The results of this study indicate that the literary Sosychology approach in the novel Disini Cinta Pertama Kali Bersemi. Is an emancipation character of the main character who tells the romance of emancipation of a woman who has steadfastly championed her rights and obligations starting from education and love life.Keywords: Field of Literature.